2011
DOI: 10.1080/10916460903468435
|View full text |Cite
|
Sign up to set email alerts
|

The Aromatization of Different FCC Naphtha Fractions over a P-Zn/HZSM-5 Catalyst

Abstract: The aromatization reaction performance of P-Zn/HZSM-5 catalyst was investigated on a fixed bed reactor using five fluid catalytic cracked (FCC) gasoline fractions (<100 ı C, 50 ı C-100 ı C, <120 ı C, 75 ı C-120 ı C, and full fraction) as feedstock, and the effect of feedstock on aromatization is discussed. The results showed that the activity and stability of P-Zn/HZSM-5 catalyst for the aromatization of the 50 ı C-100 ı C fraction were high in definite reaction conditions. After 16 hr, the content of olefin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…For the ZnHZ catalyst, the zinc content denitely decreased from 0.73% to 0.53% aer rst run. It is also conrmed that the loss of zinc 15,[29][30][31] took place for ZnHZ catalyst, while the ZnPHZ catalyst stabilized the phosphorus and zinc by the form of isolated zinc phosphate groups and further extended the ZnPZ catalyst recycle regeneration times above 20 can be seen in Fig. S10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the ZnHZ catalyst, the zinc content denitely decreased from 0.73% to 0.53% aer rst run. It is also conrmed that the loss of zinc 15,[29][30][31] took place for ZnHZ catalyst, while the ZnPHZ catalyst stabilized the phosphorus and zinc by the form of isolated zinc phosphate groups and further extended the ZnPZ catalyst recycle regeneration times above 20 can be seen in Fig. S10.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that the combination of P-modied HZSM-5 catalyst and Zn/ HZSM-5 catalyst could enable both the enhancement of hydrothermal stability and aromatics selectivity of MTA catalysts. Several groups have reported that adding phosphorus to Zn/HZSM-5 promotes the activity and stability of the catalysts in light alkane aromatization by decreasing the loss of zinc, [29][30][31] as well as in aromatization of uid catalytic cracking (FCC) fractions. [31][32][33][34] There are only a handful of ZnPHZ catalyst types used in MTA reaction, 35,36 and most of such reports have been focused on the reaction studies, not the catalyst structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the aromatic yield with an increase in temperature and a decrease in pressure during the aromatization of FCC gasoline fractions (<100, 50–100, < 120, and 75–120 °C and the entire fraction) over a Zn–P/ZSM-5 catalyst was reported. , The use of the FCC gasoline fraction (50–100 °C) resulted in the highest aromatic yield (80%), whereas the use of the entire fraction resulted in the lowest aromatic yield (24%). The Zn–P/ZSM-5 catalyst was further modified , via the dealumination of ZSM-5 using steam at 450–650 °C and then used in the aromatization of FCC naphtha (50–100 °C). The catalyst wherein HZSM-5 was pretreated with steam at 550 °C exhibited the optimal aromatization performance.…”
Section: Aromatization Catalystsmentioning
confidence: 99%
“…80,81 The use of the FCC gasoline fraction (50−100 °C) resulted in the highest aromatic yield (80%), whereas the use of the entire fraction resulted in the lowest aromatic yield (24%). The Zn− P/ZSM-5 catalyst was further modified 82,83 via the dealumination of ZSM-5 using steam at 450−650 °C and then used in the aromatization of FCC naphtha (50−100 °C). The catalyst wherein HZSM-5 was pretreated with steam at 550 °C exhibited the optimal aromatization performance.…”
Section: Isomerization Of N-cmentioning
confidence: 99%